3m-10=2(4m-s)

Simple and best practice solution for 3m-10=2(4m-s) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m-10=2(4m-s) equation:


Simplifying
3m + -10 = 2(4m + -1s)

Reorder the terms:
-10 + 3m = 2(4m + -1s)
-10 + 3m = (4m * 2 + -1s * 2)
-10 + 3m = (8m + -2s)

Solving
-10 + 3m = 8m + -2s

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-8m' to each side of the equation.
-10 + 3m + -8m = 8m + -8m + -2s

Combine like terms: 3m + -8m = -5m
-10 + -5m = 8m + -8m + -2s

Combine like terms: 8m + -8m = 0
-10 + -5m = 0 + -2s
-10 + -5m = -2s

Add '10' to each side of the equation.
-10 + 10 + -5m = 10 + -2s

Combine like terms: -10 + 10 = 0
0 + -5m = 10 + -2s
-5m = 10 + -2s

Divide each side by '-5'.
m = -2 + 0.4s

Simplifying
m = -2 + 0.4s

See similar equations:

| 79-5x=31x+15 | | x=173+173 | | 5/2(w-1)=15 | | 2xy(3x+2)-4xy(x+4)= | | 5.4q-4.9-5.8q=1.4q-3.3 | | m-8n+m+8n= | | 5.4q-4.9-5.8q=-1.4q-3.3 | | 2x+1x+5= | | 76a^2+34a+4=0 | | 6x+7=-143-9x | | 2x-0.125x+5=35 | | 4y=2y-14 | | 7-9x-2=-60+4x-13 | | 4x-3(x+1)=7 | | 4s-27=7(s-4) | | -4(6-x)+4=4-6(x+2) | | 48-2x=7x+23 | | 5-(4-a)=2a | | -14n+16=-12n-16 | | 5x-7=3x+15 | | 140-5x=31+16 | | 3(q+4)+4q+1= | | 7(2v+1)-3(9v+2)=40 | | -9=517n | | 3-2(x-2)=10 | | 8-7x=178-42x | | x+8000=70006 | | 8x+23-4=36 | | 4x+21=14x-29 | | x+8000=7000642 | | 4x+8=38 | | x-12=5x-4 |

Equations solver categories